2012
DOI: 10.1016/j.tem.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnin: at the crossroads of clocks and metabolism

Abstract: Many aspects of metabolism exhibit daily rhythmicity under the control of endogenous circadian clocks, and disruptions in circadian timing result in dysfunctions associated with the metabolic syndrome. Nocturnin (Noc) is a robustly rhythmic gene that encodes a deadenylase thought to be involved in the removal of polyA tails from mRNAs. Mice lacking the Noc gene display resistance to diet-induced obesity and hepatic steatosis, due in part to reduced lipid trafficking in the small intestine. In addition, Noc app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 69 publications
1
55
0
1
Order By: Relevance
“…Among the 94 identified regions, a fragment on chromosome 19 is largest and extends over 1.6 Mb (P < 0.01). Within this fragment, the F ST value peak (chr19.6599631, F ST = 0.84) was located about 6 kb downstream from CCRN4L, a gene regulating the circadian clock with maximal level in early evening, which has also been implicated in lipid metabolism, adipogenesis, glucose homeostasis, inflammation, and osteogenesis (review see [Stubblefield et al 2012]). Archeological and genetic evidence suggests that the dog was domesticated 16,000 or more years ago (Clutton-Brock 1995; Sablin and Khlopachev 2002;Pang et al 2009).…”
Section: Candidate Regions Under Artificial Selection In Native Dogsmentioning
confidence: 99%
“…Among the 94 identified regions, a fragment on chromosome 19 is largest and extends over 1.6 Mb (P < 0.01). Within this fragment, the F ST value peak (chr19.6599631, F ST = 0.84) was located about 6 kb downstream from CCRN4L, a gene regulating the circadian clock with maximal level in early evening, which has also been implicated in lipid metabolism, adipogenesis, glucose homeostasis, inflammation, and osteogenesis (review see [Stubblefield et al 2012]). Archeological and genetic evidence suggests that the dog was domesticated 16,000 or more years ago (Clutton-Brock 1995; Sablin and Khlopachev 2002;Pang et al 2009).…”
Section: Candidate Regions Under Artificial Selection In Native Dogsmentioning
confidence: 99%
“…Accordingly, we found that lipid absorption in the wild-type mice was strongly circadian, with rapid appearance of newly ingested lipoprotein particles into the circulation when the mice were gavaged with olive oil at night, but slow and limited appearance when olive oil was administered during the day. In contrast, the NocÀ/À mice had no rhythm in absorption and exhibited slow "daytime-like" absorption profiles following gavage given both night and day (Douris et al 2011;Stubblefield et al 2012). Furthermore, the enterocytes in the NocÀ/À mice accumulated large cytoplasmic lipid droplets, suggesting that dietary lipids were stored in these cells when Nocturnin was not present-at all times in the NocÀ/À cells or during the daytime in wild-type mice.…”
Section: Loss Of Nocturnin Results In Broad Metabolic Changesmentioning
confidence: 95%
“…Nocturnin was identifi ed as a RNA transcript that shows signifi cant circadian expression in the early part of the night in the retina of Xenopus ( 84,85 ). Nocturnin is an exoRNase that deadenylates mRNA with specifi city toward poly(A) nucleotides.…”
Section: Nocturninmentioning
confidence: 99%